JBrowse 2: a modular genome browser with views of synteny and structural variation - Diesh, Colin; Stevens, Garrett J; Xie, Peter; De Jesus Martinez, Teresa; Hershberg, Elliot A.; Leung, Angel; Guo, Emma; Dider, Shihab; Zhang, Junjun; Bridge, Caroline; Hogue, Gregory; Duncan, Andrew; et al. (Genome Biology, 2023)
We present JBrowse 2, a general-purpose genome annotation browser offering enhanced visualization of complex structural variation and evolutionary relationships. It retains core features of JBrowse while adding new views for synteny, dotplots, breakpoints, gene fusions, and whole-genome overviews. It allows users to share sessions, open multiple genomes, and navigate between views. It can be embedded in a web page, used as a standalone application, or run from Jupyter notebooks or R sessions. These improvements are enabled by a ground-up redesign using modern web technology. We describe application functionality, use cases, performance benchmarks, and implementation notes for web administrators and developers.